The cinema of attractions reloaded - Strauven, Wanda (Film culture in transition., 2006)
Twenty years ago, noted film scholars Tom Gunning and Andre; Gaudreault introduced the phrase "cinema of attractions" to describe the essential qualities of films made in the medium's earliest days, those produced between 1895 and 1906. Now, The Cinema of Attractions Reloaded critically examines the term and its subsequent wide-ranging use in film studies. The collection opens with a history of the term, tracing the collaboration between Gaudreault and Gunning, the genesis of the term in their attempts to explain the spectacular effects of motion that lay at the heart of early cinema, and the pair's debts to Sergei Eisenstein and others. This reconstruction is followed by a look at applications of the term to more recent film productions, from the works of the Wachowski brothers to virtual reality and video games. With essays by an impressive collection of international film scholars - and featuring contributions by Gunning and Gaudreault as well - The Cinema of Attractions Reloaded will be necessary reading for all scholars of early film and its continuing influence